Teachers Assessment of Young Learners English Productive Skills - Amalia, Suci Nugrah (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Assessing the productive skills namely speaking and writing tends to be more difficult than assessing the receptive skills namely listening and reading. The teachers need to pay more attention in assessing these skills especially for the elementary school students who are in the beginner level of English ability. Therefore, the aims of this research were to find out : The test format, marking criteria and the scoring scheme used by the teachers in assessing students productive skills. This research was conducted under descriptive design. The respondents were 2 English teachers of Sekolah Dasar Islam Terpadu Aisyiyah (SDITA) Taman Harapan Curup. The data were taken from observation, interview and document analysis. The results of this research were : 1) The test formats used by the teachers to assess speaking skill wereinterview, picture description, and presentation while composition, brief description, writing the interview result and writing the expression were used to assess writing skill. 2) The criteria used by the teachers were pronunciation, vocabulary and fluency for speaking assessment, grammar, vocabulary and mechanics for writing assessment, 3)The teacher use the scoring scale to score students productive skills. The scale itself depends on the criteria or language component which were being assessed and each scale of score has its own description. Virtually, it would be better if the teachers write down some notes in students writing product so that they can analyze their weakness easily.